Vulnerable period in heart failure: a window of opportunity for the optimization of treatment - a statement by Mexican experts - José Antonio Magaña Serrano; José Angel Cigarroa López; Adolfo Chávez Mendoza; Juan Betuel Ivey-Miranda; Genaro Hiram Mendoza Zavala; Luis Olmos Domínguez; Sergio Armando Chávez Leal; José Ernesto Pombo Bartelt; Eduardo Heberto Herrera-Garza; Gerardo Mercado Leal; Rodolfo Parra Michel; Luisa Fernanda Aguilera Mora; et al. (BioExcel Publishing Ltd, 2024)
Acute heart failure (HF) is associated with poor prognosis. After the acute event, there is a vulnerable period during which the patient has a marked risk of readmission or death. Therefore, early optimization of treatment is mandatory during the vulnerable period. The objective of this article is to provide recommendations to address the management of patients with HF during the vulnerable period from a practical point of view. A group of Mexican experts met to prepare a consensus document. The vulnerable period, with a duration of up to 6 months after the acute event - either hospitalization, visit to the emergency department or the outpatient clinic/day hospital - represents a real window of opportunity to improve outcomes for these patients. To best individualize the recommendations, the management strategies were divided into three periods (early, intermediate and late vulnerable period), including not only therapeutic options but also evaluation and education. Importantly, the recommendations are addressed to the entire cardiology team, including physicians and nurses, but also other specialists implicated in the management of these patients. In conclusion, this document represents an opportunity to improve the management of this population at high risk, with the aim of reducing the burden of HF.